Penerapan Teknologi Pengeringan Kabinet dan Kulkas display untuk Meningkatkan Daya Saing UMKM Olahan Gatot di Sumberpucung, Kabupaten Malang Indonesia - Adrian Hartanto Darma Sanputra; Apriana Rahmawati; Evi Fitriana; Ervina Dwi Aprilia; Ghina Mufidatus Salma (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2026)
Gatot, a fermented-cassava food, is the culinary icon of Gatot Tourism Village in Sumberpucung Subdistrict, Malang Regency. Cafe Koka, the pioneering gatot business in the area, faces two problems that hold back its growth. Its drying process still relies on sunlight, so production stops during the rainy season and the failure rate reaches 30–40%, while product presentation lacks adequate display facilities, lowering its appeal and selling value. This community-service program installed a 5 kg-per-batch cabinet dryer and two display refrigerators, accompanied by dried-gatot packaging development and staff training. The work followed a Plan-Do-Check-Act cycle combined with participatory mentoring over eight months, evaluating production and marketing indicators. After the program, drying time dropped from 2–4 days to about 4–5 hours, the product failure rate fell to 8–10%, and drying uniformity rose to about 90%. On the marketing side, impulse purchases increased by more than 40%, customer satisfaction with product display reached 4.5 of 5 (n=50), and monthly revenue grew about 175% owing to the new packaged-gatot line. Combining production and marketing technology strengthened the self-reliance of this local-food micro-enterprise.